Teacher training and communicative rationality: intersection points (Revista Internacional de Formação de Professores, 2020)
Discusses the process of continuing education for the technical teacher, at one of the State Centers for Vocational Education, in the Sisal Identity Territory, and the contribution of this teacher's professionality, from a reflective character of pedagogical conceptions. It aims to understand how these processes collaborate to overcome the instrumental rationality of teachers with a view to communicative rationality. Methodologically, it is anchored in a collaborative research, developed from reflective sessions with teachers about their teaching practice. As a result, it is pointed out the importance of training processes through emancipatory relation, enable teaching practices based on communicative action.
Keywords: Teacher training.; Communicative rationality.; Professional Education.